Analisis Efektivitas Pajak Parkir dalam Meningkatkan Pendapatan Asli Daerah di Wilayah Jakarta Selatan - Wening Estiningsih; Heri Nurranto (Sosio e-Kons, 2020)
In accordance with the regional taxation system which was started in 1997 by issuing Law Number 18 of 1997 concerning building a simple, fair, and effective regional levy system. This reform is aimed at building a fair, simple, and effective local levy system, as well as correcting the weaknesses of the previous system, especially those related to the effectiveness and efficiency of tax collection. The third phase was marked by the issuance of Law Number 25 of 1999 concerning Central and Regional Financial Balancing, which has significantly changed the financial relations between the central government and regional governments, which were from more centralized to decentralized. This phase is marked by the existence of regional autonomy. One of them is the parking tax revenue which is currently managed by the government, private sector, and individually so that the effectiveness of parking tax revenue can be seen on the contribution of local tax revenue. As for this research, using a descriptive research method and after conducting the research it was concluded that it was in accordance with the expected target. However, it would be maximized if all elements of the parking tax were maximized, namely, the amount of parking revenue from illegal parking was Rp. 19,720,000,000. If the nominal is added to the parking tax revenue in 2018, which is Rp. 195,281,205,961 to Rp. 215,001,205,961.